Supporting the spirituality of older people living with dementia in nursing care: A hermeneutic phenomenological inquiry into older people's and their family members' experiences - Toivonen Kristiina; Charalambous Andreas; Suhonen Riitta (WILEY, 2022)
Background: Supporting spirituality is an essential aspect of the holistic nursing care of older people living with dementia. Spirituality is defined as a search for answers to questions about the meaning and purpose of life and the individual's relationship with the sacred or transcendent. This relationship may or may not involve an affiliation with a specific religion.Objective: To understand how older people living with dementia and their family members experience spirituality and its support in nursing care.Design: A qualitative study informed by the principles of Ricoeurian hermeneutic phenomenology.Settings: We conducted the study in home care and long-term care settings in Southern Finland.Participants: We collected data between 2017-2020 from a purposive sample of 10 older people living with dementia and their 9 family members (n = 19).Methods: We used interviews to collect data and adapted and used Ricoeur's theory of interpretation as a method for analysis.Results: The findings of this study show that older people living with dementia need spiritual support in nursing care based on their personal understanding of spirituality. The four elements of this spirituality that emerged were: religion, meaningful relationships, nature, and art. The participants addressed some challenges to spiritual support in the nursing care of older people living with dementia including: the competence and abilities of nursing, time available, presence and experience.Conclusions: Older people living with dementia and their family members consider spiritual support an important aspect of nursing care. To support the spirituality of these older people, the elements of spirituality need to be understood as these are central to each person's spiritual position. Additionally, spiritual support requires understanding knowledge, experience, time and presence, to manage all four elements with individuals.